2016
DOI: 10.1242/dev.128595
|View full text |Cite
|
Sign up to set email alerts
|

NO FLOWERING IN SHORT DAY (NFL) is a bHLH transcription factor that promotes flowering specifically under short-day in Arabidopsis

Abstract: Flowering in plants is a dynamic and synchronized process where various cues including age, day length, temperature and endogenous hormones fine-tune the timing of flowering for reproductive success. Arabidopsis thaliana is a facultative long day (LD) plant where LD photoperiod promotes flowering. Arabidopsis still flowers under shortday (SD) conditions, albeit much later than in LD conditions. Although factors regulating the inductive LD pathway have been extensively investigated, the non-inductive SD pathway… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
43
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(49 citation statements)
references
References 78 publications
4
43
0
Order By: Relevance
“…Based on analyses of fluorescence patterns obtained by expressing bHLHL093:YFP or GFP:bHLH093 under control of the cauliflower mosaic virus 35S promoter, we and others demonstrated that bHLH093 localizes to nuclei (Supplemental Fig. 4), 6 which is in accordance with the subcellular localization reported for SCREAM/ICE1 and SCREAM 2. 3 During the first 28 d post-germination under long-day growth conditions (16 h day/8 h night), the growth and development of rosette leaves occurred normally in a bhlh093-1/bhlh061-1 loss-offunction mutant.…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…Based on analyses of fluorescence patterns obtained by expressing bHLHL093:YFP or GFP:bHLH093 under control of the cauliflower mosaic virus 35S promoter, we and others demonstrated that bHLH093 localizes to nuclei (Supplemental Fig. 4), 6 which is in accordance with the subcellular localization reported for SCREAM/ICE1 and SCREAM 2. 3 During the first 28 d post-germination under long-day growth conditions (16 h day/8 h night), the growth and development of rosette leaves occurred normally in a bhlh093-1/bhlh061-1 loss-offunction mutant.…”
Section: Discussionsupporting
confidence: 87%
“…Defective bolting, as observed with the bhlh093-1/bhlh061-1 mutant, is consistent with the lack of stem growth reported for gibberellin biosynthetic mutants, 22 and it is thus possible that bHLH093 and bHLH061 serve functions in regulating gibberellin biosynthesis in the shoot apex. Sharma et al 6 reported that the gibberellin profile was affected significantly in the apex of bhlh093 mutant plants, which provides further support for the role of GA imbalances in producing the observed phenotype. However, insufficient GA supply in biosynthetic mutants results in leaves of dramatically reduced size 22 and not the increased biomass and substantial curling observed with the bhlh093-1/bhlh061-1 line.…”
Section: Progress Toward Understanding Bhlh093 and Bhlh061 Functionmentioning
confidence: 72%
See 1 more Smart Citation
“…A previous report has shown that Arabidopsis bHLH93 promotes plant flowering under short‐day conditions by regulating the expression of gibberellin biosynthesis and metabolism‐associated genes (Sharma et al ., ). Considering the fact that gibberellins are positive regulators of leaf senescence (Chen et al ., , ), it will be interesting to determine whether bHLH93 also plays a role in gibberellin‐induced leaf senescence.…”
Section: Discussionmentioning
confidence: 99%
“…To our knowledge, the role of bHLH093 in the roots and in response to light has never been characterised before. The only information concerns a role in flowering promotion under non-inductive short-day conditions through the gibberellin pathway (Sharma et al, 2016).…”
Section: Discussionmentioning
confidence: 99%